Study on numerical simulation of rock breaking by PDC wear teeth cutting - Maosheng CAI; Hongbo WANG; Chunjiang ZHANG; Sai LI; Shuting CHENG (Jin'gangshi yu moliao moju gongcheng, 2024)
Objectives: The existing literature on numerical simulation of cutters rarely considers the effect of wear height on the temperature and cutting load of cutters. However, the deterioration of force and the aggravation of thermal wear after the wear of polycrystalline diamond composite (PDC) cutters lead to their rapid failure. Therefore, it is particularly necessary to study the change of cutting load and the law of heat generation of worn cutters to extend their service life. Methods: Based on elastoplastic mechanics and rock mechanics, a 3D dynamic rotational simulation model of worn teeth is established with the Drucker-Prager criterion as the rock constitutive model. The stress state and temperature rise amplitude of cutting teeth under different wear heights, cutting depths, and front inclination angles are analyzed by numerical simulation. Results: (1) Influence of wear height on cutting load: Under simulated conditions (front inclination 15°, cutting depth 1.5 mm), the size and the fluctuation degree of cutting load increase with the increase of wear height when the wear height is 0−1.5 mm, and decrease slightly when the wear height is larger than 1.5 mm. In terms of tangential force, the cutter with a wear height of 1.5 mm is subjected to the largest tangential force, but when the wear height is 2.0 mm, the tangential force is reduced. In terms of axial force, the axial force of worn teeth is higher than that of unworn teeth. When the wear height is 0−1.5 mm, the axial force gradually increases with the increase of wear height. When the wear height is 1.5 mm, the axial force reaches its maximum, and when the wear height is larger than 1.5 mm, the axial force decreases. The axial force of the cutter with a wear height of 1.0 mm and wear height of 2.0 mm is exactly 1.2 times that of the unworn tooth, and the axial force of the cutter with a wear height of 1.5 mm is 1.3 times that of the unworn tooth. (2) Influence of cutting depth on cutting load: Under simulated conditions (wear height 1.0 mm, front inclination angle 15°), tangential force and axial force gradually increase with the increase of cutting depth, and the degree of fluctuation is more intense. In terms of tangential force, the tangential force of the worn tooth with the cutting depth of 2.0 mm is 1.9 times that of the worn tooth with the cutting depth of 1.0 mm, and the increase is larger. The tangential force of the worn tooth with the cutting depth of 1.5 mm is only 25% higher than that of the worn tooth with the cutting depth of 1.0 mm, and the increase is small. In terms of axial force, with the increase of cutting depth, the increase in axial force is relatively balanced. (3) Influence of front inclination angle on cutting load: Under simulated conditions (wear height 1.0 mm, cutting depth 1.5 mm), the cutting load of worn teeth gradually increases with the increase of front inclination angle, with the tangential force increasing by 28% and the axial force increasing by 32%. When the front angle is 10°, the fluctuation of the cutting load is more severe than at other time with 15° and 20°. (4) Influence of wear height on cutting heat: according to the temperature cloud map of the cutter, because the cutter rotates around the central axis to break rock, the linear speed of the cutting edge differs, and the temperature on the side away from the central axis will be higher than that on the side near the central axis. With the increase of wear degree, the temperature rise of the cutter becomes more significant, and the high-temperature area is concentrated in the cutting-cutter contact area, where plastic deformation and frictional heat generation are concentrated. The temperature change curve can be divided into three stages: rising period, transitional period, and stable period. With the passage of time, the temperature of the cutter continues to rise, and the temperature rise rate in the rising period is greater than in the transitional period, tending to flatten after entering the stable period. In the process of rock breaking, the temperature rise of worn teeth is much higher than that of unworn teeth, with a temperature increase of 54%−103%. Conclusions: The force on a cutter with excessive wear is more complex and variable, increasing the risk of fatigue failure. In terms of tooth layout, it can be considered to place the auxiliary cutting unit behind the main cutting unit composite sheet and make its exposure height lower than the composite sheet, which can effectively reduce the load on the main cutting gear and reduce the probability of overload damage to the cutting gear. The cutting load of the worn teeth increases with the increase of the front angle. Considering the fluctuation of cutting efficiency and load, the front angle should be controlled at 15°−20° as far as possible, which is beneficial to prolong the service life of the cutting teeth. After cutter wear, its ability to break rock is weakened, the rock pre-crushing area is reduced, and the way of cutting the rock gradually transitions from shear failure to extrusion failure, greatly reducing the rock-breaking efficiency of the cutter. In the process of cutting rock breaking, the temperature rise of the worn teeth is much higher than that of the unworn teeth, and the temperature rise increases with the increase of wear degree. Thus, the thermal wear of the cutting teeth will continue to intensify after wear, accelerating the wear and failure of the cutting teeth. In the subsequent cutting process, cutter of wear-resistant and high-temperature-resistant materials can be selected to reduce the weight on the bit and the speed of drilling while increasing the water power of the pump, effectively inhibiting thermal wear.